(untitled) (The Review of Diabetic Studies, 2024)
Background: High-quality antenatal care (ANC) is essential to reduce maternal and neonatal complications and to achieve the Sustainable Development Goals. Understanding maternal perspectives on the quality of ANC provided by nurses and healthcare assistants (HCAs) is critical for improving services. Aim of this study: To evaluate mothers’ perceptions of the quality of ANC services provided by nurses and healthcare assistants in Saudi Arabia and to identify factors associated with perceived ANC quality. Methods: A cross-sectional, facility-based study was conducted among postpartum women attending maternity units in Saudi Arabia. A structured questionnaire adapted from the WHO framework of ANC quality was used to assess three components of care: assessment, health promotion, and care provision. Results: A total of 300 mothers participated. Most reported receiving ANC from mixed teams of nurses and healthcare assistants. Mothers perceived the overall ANC quality as moderate, with no major difference between governmental and private facilities. Higher maternal education and regular ANC attendance were significantly associated with higher ANC quality scores (p < 0.05). Mode of delivery, neonatal complications, and birth weight showed no significant association with perceived ANC quality. Conclusion: Mothers in Saudi Arabia generally perceive ANC services provided by nurses and healthcare assistants as adequate but requiring improvement—particularly in health education and consistency of clinical assessments. Enhancing staff training, ensuring standardized ANC protocols, and strengthening counseling could improve maternal satisfaction and outcomes.